Graph processing in database - CHEN LIANG (2017)
The subject matter described herein relates to database middleware for enabling graph processing. A middleware between the graph data and underlying relational or SQL database is proposed. The local properties and topology information of nodes in the graph can be stored in a single node table in the database, thereby eliminating the need for a physical junction table. The middleware may efficiently translate graph queries into SQL queries over related tables. The middleware may optimize the translated queries using the topology knowledge which is oblivious to the database query engine. 本文所描述的主题涉及用于实现图处理的数据库中间件。提出了图数据和底层关系数据库或SQL数据库之间的中间件。图中的节点的局部属性和拓扑信息可以存储在数据库中的单个节点表中，从而不再需要物理联接表。中间件可以有效地将图查询转换成对相关表的SQL查询。中间件可以使用不考虑数据库查询引擎的拓扑知识来优化转换后的查询。